Neurocognitive Trajectories After 72 Weeks of First-Line Anti-retroviral Therapy in Vietnamese Adults With HIV-HCV Co-infection - Paul, Robert H.; Shikuma, Cecilia M.; Chau, Nguyen Van Vinh; Ndhlovu, Lishomwa C.; Thanh, Nguyen Tat; Belden, Andrew C.; Chow, Dominic C.; Chew, Glen M.; Premeaux, Thomas A.; Ly, Vo Trieu; McBride, Joseph A. D.; Bolzenius, Jacob D.; et al. (Frontiers in Neurology, 2021)
Background: Long-term neurocognitive outcomes following first-line suppressive antiretroviral therapy (ART) remain uncertain for individuals with HIV and hepatitis C (HCV) co-infection. The study examined neurocognitive performance before and after 72 weeks of ART using repeated multivariate analyses and latent trajectory models. Methods: 160 adults with chronic, untreated HIV infection (n=80 with HCV co-infection and n=80 HIV mono-infected) and 80 demographically similar healthy controls were recruited from the Hospital for Tropical Diseases in Ho Chi Minh City and the surrounding community, respectively. Neurocognitive measures (adapted for use in Vietnam) and liver enzyme tests were compared across groups at baseline. Repeated multivariate and group-based trajectory analyses (GBTA) examined neurocognitive subgroup profiles of the co-infected individuals after 72 weeks of de novo efavirenz- (n=41) or raltegravir-based (n=39) ART. Results: Baseline analyses revealed worse motor function in HIV-HCV co-infected individuals compared to both comparison groups. Longitudinal analyses revealed improved neurocognitive performance by week 48 for most participants regardless of treatment arm. GBTA identified a subgroup (35% of HIV-HCV sample) with persistent motor impairment despite otherwise successful ART. Higher HIV viral load and lower CD4+ T cell count at baseline predicted persistent motor dysfunction. Liver indices and ART regimen did not predict neurocognitive outcomes in HIV-HCV co-infected individuals. Conclusions: Most HIV-HCV co-infected individuals achieve normative neurocognitive performance after 48 weeks of de novo suppressive ART. However, individuals with more severe HIV disease prior to ART exhibited motor impairment at baseline and 72 weeks after otherwise successful treatment. Interventions aimed at improving motor symptoms at the time of HIV treatment onset may improve long-term clinical outcomes in HIV-HCV co-infected adults.